ANALYZING THE CRITICAL EFFECTS OF CAR, LDR, NPL, AND BOPO ON ROA IN THE BANKING INDUSTRY - Muhamad Rohan; Nur Suci I Mei Murni (Reviu Accounting, Business & Organizations, 2025)
Research Objective – The purpose of this study is to determine the effect of CAR, LDR, NPL, and BOPO on ROA in the National Private Commercial Bank sector for the period 2019–2021. Method – This research uses a quantitative method with a population of conventional banks, and the sample consists of foreign exchange national private banks registered with the Financial Services Authority (OJK) for 2019–2021. The sampling technique used is purposive sampling; the data used in this study is secondary data, which is processed using the SPSS testing tool. Findings – The banking industry is a financial institution that functions as a financial intermediary; the business operations of banks are based on the trust of their customers. In their operations, banks rely more heavily on customer funds compared to the bank's own capital or shareholder funds, which is why, as managers, banks are required to maintain a sound level of financial health to keep the wheels of the economy turning. Theoretical and Policy Implications – The findings of this research can be utilized by investors as a consideration when investing in banking companies. Research Novelty – This study addresses and improves upon the research gap found in previous studies.